Financial markets and institutions /Frederic S Mishkin, Stanley G Eakins. - Mishkin, Frederic S.
Examines models and concepts through the eyes of a practicing financial manager to see not only why they matter, but also how they are used in the real world. This book offers coverage of valuation concepts, more quantitative material, and a streamlined, finance-focused presentation